Comité Pro-Monumento: Lcdo Federico Degetau y González - Todd, Roberto H.; Goyco, Ramón G.; Montull, Eduardo; Blanco, J. P.; Lecomple, Eugenio; Vivas Valdivieso, Guillermo; Diaz, Román (My University, 2015)
Comité Pro-Monumento: Lcdo Federico Degetau y González
Keywords: Degetau y González, Federico, 1862-1914; Veve y Calzada, Santiago, 1848-1898; Huyke, Juan B., 1880-1961; Sánchez, Bonifacio